Evaluation of SNPs in miR-196-a2, miR-27a and miR-146a as risk factors of colorectal cancer - Hezova, Renata; Kovarikova, Alena; Bienertova-Vasku, Julie; Sachlova, Milana; Redova, Martina; Vasku, Anna; Svoboda, Marek; Radova, Lenka; Kiss, Igor; Vyzula, Rostislav; Slaby, Ondrej (World journal of gastroenterology, 2012)
AIM: To investigate whether selected single nucleotide polymorphisms (SNPs) in miR-196a2, miR-27a and miR-146a genes are associated with sporadic colorectal cancer (CRC). METHODS: In order to investigate the effect of these SNPs in CRC, we performed a case-control study of 197 cases of sporadic CRC and 212 cancer-free controls originating from the Central-European Caucasian population using TaqMan Real-Time polymerase chain reaction and allelic discrimination analysis. RESULTS: The genotype and allele frequencies of SNPs were compared between the cases and the controls. None of the performed analysis showed any statistically significant results. CONCLUSION: Our data suggest a lack of association between rs11614913, rs895819 and rs2910164 and colorectal cancer risk in the Central-European Caucasian population, a population with an extremely high incidence of sporadic colorectal cancer.
Keywords: senioři; běloši; Genetic Predisposition to Disease; Real-Time Polymerase Chain Reaction; jednonukleotidový polymorfismus; Male; kolorektální nádory; Incidence; Česká republika; mikro RNA; Risk Assessment; Middle Aged; Colorectal Neoplasms; mužské pohlaví; studie případů a kontrol; adenokarcinom; incidence; MicroRNA; Czech Republic; MicroRNAs; kvantitativní polymerázová řetězová reakce; logistické modely; Polymorphism, Single Nucleotide; Colorectal cancer; ženské pohlaví; hodnocení rizik; Single nucleotide polymorphism; Humans; odds ratio; Chi-Square Distribution; lidé středního věku; frekvence genu; rozdělení chí kvadrát; rizikové faktory; Logistic Models; White People; Gene Frequency; genetická predispozice k nemoci; Association study; Female; Aged; Risk Factors; Adenocarcinoma; lidé; Case-Control Studies; Odds Ratio